2020
DOI: 10.3390/w12113192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angle between Pier and Center of River Flow on Local Scouring around the Bridge Pier

Abstract: In recent years, heavy rainfall disasters have caused frequent damage to bridge piers due to scouring and have resulted in the fall of bridges in many areas in Japan. The objective of this study was to investigate the effect of local scouring around the downstream of the piers on the local scouring around the center of the river flowing at an angle to the piers. It was found that when the center of the river flows at an angle to the piers, the scouring area becomes wider from the upstream to the downstream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Further, in Case 13, the range of the local scour hole formed upstream of the bridge pier model increased as the water level rose and fell iteratively, and the local scouring extended downstream of the oval specimen more widely than that when θ = 30 • at the left side. This tendency was similar to that of the experiments previously conducted by the authors and other researchers [16][17][18]. From these figures, it can be observed that the local scour depth increases as the water level rises and falls iteratively, and that the increase tends to converge after the third or fourth water flow.…”
Section: Progression Of the Local Scour Areasupporting
confidence: 90%
See 1 more Smart Citation
“…Further, in Case 13, the range of the local scour hole formed upstream of the bridge pier model increased as the water level rose and fell iteratively, and the local scouring extended downstream of the oval specimen more widely than that when θ = 30 • at the left side. This tendency was similar to that of the experiments previously conducted by the authors and other researchers [16][17][18]. From these figures, it can be observed that the local scour depth increases as the water level rises and falls iteratively, and that the increase tends to converge after the third or fourth water flow.…”
Section: Progression Of the Local Scour Areasupporting
confidence: 90%
“…Figures [13][14][15][16][17][18] show the changes in the local scour length obtained from the experiment. The local scour extension shown in the figures is the distance from the starting point of the pier model to the point where the ground level reaches the surface of the soil layer in the measurement direction.…”
Section: Effect Of Water Level History and Pier Shape On Local Scour Lengthmentioning
confidence: 99%
“…The potential techniques also showed by Bento et al (2018), which used Kinect sensor and closerange photogrammetry for semi rounded shape scour modelling that most common used in Portugal. Previous studies have been researched to investigate the flow pattern and scouring by modelling software (Ali et al, 2017;Kadono et al, 2020;Lee et al, 2019). Therefore, it is of utmost importance to consider different types of pier shapes and determine the most suitable pier geometry in terms of reducing scour (Al-Shukur & Obeid, 2016;Melville, 1997;Murtaza et al, 2018;Török et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 19 experimentally investigated the scour on a single elongated rectangular shaped slab pier skewed into a shallow stream. Through experiments on a thick rectangular pier, Kadono et al 20 showed that the scour area is enlarged when skew is toward the river flow, considering the collapse of a railroad bridge. Sato 6 experimentally investigated the effect of a skewed spindle shape on the scour and water level changes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, structures, such as piles, placed below the bottom of the pier may influence the scour depth 17 , 18 . In addition, the degree of scour is more severe when the pier is skewed relative to the center of flow, regardless of the installation or hydraulic conditions 6 , 20 , 21 . In practice, a combination of several conditions affect the pier structure rather than the independent action of single factors.…”
Section: Introductionmentioning
confidence: 99%